Fentanyl and other opioid involvement in methamphetamine-related deaths. (4th March 2022) - Dai, Zheng; Abate, Marie A.; Groth, Caroline P.; Rucker, Tori; Kraner, James C.; Mock, Allen R.; Smith, Gordon S.
ABSTRACT: Background : Methamphetamine-related deaths have been rising along with those involving synthetic opioids, mostly fentanyl and fentanyl analogs (FAs). However, the extent to which methamphetamine involvement in deaths differs from those changes occurring in synthetic opioid involvement is unknown. Objectives : To determine the patterns and temporal changes in methamphetamine-related deaths with and without other drug involvement. Methods : Data from all methamphetamine-related deaths in West Virginia from 2013 to 2018 were analyzed. Quasi-Poisson regression analyses over time were conducted to compare the rates of change in death counts among methamphetamine and fentanyl//FA subgroups. Results : A total of 815 methamphetamine-related deaths were analyzed; 572 (70.2%) were male and 527 (64.7%) involved an opioid. The proportion of methamphetamine only deaths stayed relatively flat over time although the actual numbers of deaths increased. Combined fentanyl/FAs and methamphetamine were involved in 337 deaths (41.3%) and constituted the largest increase from 2013 to 2018. The modeling of monthly death counts in 2017–2018 found that the average number of deaths involving fentanyl without methamphetamine significantly declined (rate of change −0.025, p < .001), while concomitant fentanyl with methamphetamine and methamphetamine only death counts increased significantly (rate of change 0.056 and 0.057, respectively, p < .001). Conclusions : Fentanyl and FAs played an increasingly significant role in methamphetamine-related deaths. The accelerating number of deaths involving fentanyl/FAs and methamphetamine indicates the importance of stimulants and opioids in unintentional deaths. Comprehensive surveillance efforts should continue to track substance use patterns to ensure that appropriate prevention programs are undertaken.